Proinflammatory cytokines profile in patients with Rheumatoid arthritis - Saleh, Shahlaa M.; Zangor, Jabbar R. (Journal of the Faculty of Medicine Baghdad, 2009)
Background:Rheumatoid arthritis (RA) is a chronic, inflammatory autoimmune disorder that causes the immune system to attack the joints. It is a disabling and painful inflammatory condition, which can lead to substantial loss of mobility due to pain and joint destruction. RA is a systemic disease, often affecting extra-articular tissues throughout the body including the skin, blood vessels, heart, lungs, and muscles. Patients and Methods: Enzyme immunoassay for Determination of human TNF- , IL-1 and GM-CSF in serumsamples from50 patients with a diagnosis of rheumatoid arthritisResults: of cytokines showed a significant increase in TNF-alpha, IL-1 beta and GM-CSF in patients with rheumatoid arthritis (70.98 12.08) pg/ml,(238.6 116.4)pg/ml and (96.1 12.08)pg/ml respectively. When compared with the control group (7.0 3.09)pg/ml, (15.4 3.8)pg/ml and (6.8 3.03)pg/ml respectively.Conclusion: Increased serum levels of proinflammatory cytokine such as TNF- , IL-1 and GM-CSF probably play important role in driving inflammatory process and promoting joint destruction in rheumatoid arthritis. Regulation of these cytokines is a crucial importance in the RA disease showing pleiotropic actions and many different targets.